Detection of anti-3AB3 non-structural protein antibodies in foot-and-mouth disease virus vaccinated buffaloes at a semi-organized farm of Madhya Pradesh in India - Audarya, Sachin Digambar; Dahiya, Swati; Lather, Anshul; Chhabra, Daljeet; Sikrodia, Ravi; Kumar Kakker, Naresh; Kapoor, Sanjay; Gangil, Rakhi; Jogi, Joycee; Sharda, Rakesh (Buffalo Bulletin, 2024)
Foot-and-mouth disease (FMD), one of the most important viral diseases of cloven-hoofed animals in India, is caused by FMD virus (FMDV) which belongs to Aphthovirus in the family Picornaviridae. There are three serotypes of FMDV (O, A and Asia 1) circulating amongst the livestock population of India. FMD is characterized by the formation of vesicles especially over the tongue and in between the interdigital space. FMD-affected animals with tongue lesions are reluctant to feed and subsequently yield less milk as well as affected animals never regain their production status causing huge economic losses to the animal owners. In the present study, random whole blood samples from FMD-vaccinated 38 adult buffaloes were collected in sterile containers of a semi-organized buffalo farm of Madhya Pradesh in India. Purified FMD vaccines only elicit antibodies (that are protective) against structural proteins of FMDV while natural FMDV infection invokes antibodies against both structural and non-structural proteins. Serum samples were employed in recombinant 3AB3 non-structural protein-based enzyme-linked immunosorbent assay (3AB3 NSP-ELISA kit provided by ICAR-Directorate of FMD, Mukteshwar) for differentiation of FMD-infected and vaccinated animals (DIVA). A total of 10.53% (4/38) serum samples tested positive in DIVA. Largely the vaccinated animals remained protected as no clinical signs of the disease were observed reiterating the importance of regular FMDV vaccination in animals at semi-organized dairy farms.